Religion and Military: Communication Synergy and Collaboration in Blue Economy Development Program in Indonesia - Chamidah, Nurul; Rosyidi, Moh. Imron; Suwarno, Panji; Putra, Andri Azis (Manunggal Halim Jaya, 2025)
Indonesia possesses vast maritime potential, notably exemplified by the mangrove ecosystems along its coastal regions. The effective management of marine resources necessitates an integrated and comprehensive model. This necessity has predominantly been addressed through the blue economy framework. The defense of national territory inherently involves military engagement; however, sole management of coastal areas by the military presents potential challenges. Consequently, the involvement of religious groups is essential to facilitate communication and promote the blue economy initiatives within these coastal zones. This study's primary objective is to enhance coastal communities' welfare through the synergy between religious institutions and military forces. The findings indicate that spiritual and military entities have independently undertaken mangrove conservation efforts. While both parties acknowledge the necessity of collaborative action for developing a mangrove-based blue economy, such collaboration has yet to be realized due to the absence of a formal legal framework. The synergy between religious groups and the military occurs organically, rooted in a shared historical legacy of contributing to the formation of the Indonesian nation and supporting national development efforts. Effective program collaboration requires the presence of development actors capable of serving as catalysts to unify these two sectors. Mangrove conservation activities remain largely ceremonial, lacking structured oversight and sustainability measures for implementing a comprehensive, role-specific, and goal-oriented program.